Escherichia coli O157:H7 tir 255 T > A allele strains differ in chromosomal and plasmid composition - Weinroth, Margaret D.; Clawson, Michael L.; Harhay, Gregory P.; Eppinger, Mark; Harhay, Dayna M.; Smith, Timothy P. L.; Bono, James L. (Frontiers in Microbiology, 2023)
Shiga toxin-producing Escherichia coli (STEC) O157:H7 strains with the T allele in the translocated intimin receptor polymorphism (tir) 255 A > T gene associate with human disease more than strains with an A allele; however, the allele is not thought to be the direct cause of this difference. We sequenced a diverse set of STEC O157:H7 strains (26% A allele, 74% T allele) to identify linked differences that might underlie disease association. The average chromosome and pO157 plasmid size and gene content were significantly greater within the tir 255 A allele strains. Eighteen coding sequences were unique to tir 255 A allele chromosomes, and three were unique to tir 255 T allele chromosomes. There also were non-pO157 plasmids that were unique to each tir 255 allele variant. The overall average number of prophages did not differ between tir 255 allele strains; however, there were different types between the strains. Genomic and mobile element variation linked to the tir 255 polymorphism may account for the increased frequency of the T allele isolates in human disease.